Alpha subunit variants of the human glycine receptor: primary structures, functional expression and chromosomal localization of the corresponding genes - Grenningloh, G.; Schmieden, V.; Schofield, P.R.; Seeburg, P.H.; Siddique, T.; Mohandas, T.K.; Becker, C.M.; Betz, H. (The EMBO journal, 1990)
Two cDNAs encoding variants (alpha 1 and alpha 2) of the strychnine binding subunit of the inhibitory glycine receptor (GlyR) were isolated from a human fetal brain cDNA library. The predicted amino acid sequences exhibit approximately 99% and approximately 76% identity to the previously characterized rat 48 kd polypeptide. Heterologous expression of the human alpha 1 and alpha 2 subunits in Xenopus oocytes resulted in the formation of glycine‐gated strychnine‐sensitive chloride channels, indicating that both polypeptides can form functional GlyRs. Using a panel of rodent‐human hybrid cell lines, the gene encoding alpha 2 was mapped to the short arm (Xp21.2‐p22.1) of the human X chromosome. In contrast, the alpha 1 subunit gene is autosomally located. These data indicate molecular heterogeneity of the human GlyR at the level of alpha subunit genes.